Photocrosslinked hybrid composites with Ag, Au or Au-Ag NPs as visible-light triggered photocatalysts for degradation/reduction of aromatic nitroderivatives. (December 2019) - Melinte, Violeta; Stroea, Lenuta; Buruiana, Tinca; Chibac, Andreea L.
Graphical abstract: Highlights: Noble metal nanoparticles (Au, Ag) were in situ photogenerated in organic matrices. Catalytic materials were achieved by simple, green and efficient photopolymerization process. Photocatalytic degradation of 4-nitroaniline under visible irradiation was tested. Photoreduction of 4-nitroaniline to p-phenylenediamine without extra addition of reducing agent was performed. Abstract: Flexible free-standing nanocomposite films embedding Ag, Au or Au-Ag nanoparticles were successfully synthesized by a simple one-pot process, namely photocrosslinking of organic matrix in tandem with photogeneration of noble metal nanoparticles, both initiated by Irgacure 819 photoinitiator. The achieved materials were characterized by UV-vis spectroscopy and transmission electron microscopy, in order to evaluate the morphology, size and shape of the prepared metallic catalysts. The photocatalytic activity of the obtained catalysts was evaluated following the photodegradation of 4-nitroaniline under ambient conditions and visible irradiation or the photoreduction of 4-nitroaniline to p -phenylendiamine in the presence of NaBH4 . Further modification of the organic matrix by the inclusion of 3-acrylamidophenylboronic acid monomer, allowed us to prepare a catalyst with the hydrogen donor compound embedded in the polymer film. The photoreduction of 4-nitroaniline to p -phenylenediamine occurred in the presence of the new photocatalyst without the addition of a reducing agent in the reaction mixture, although the reaction is slower than that accomplished in the presence of NaBH4 .